EFFECTS OF PLANTING PERIODS ON PRODUCTIVE TILLERING AND PRODUCTIVE STALKS OF DURUM WHEAT CULTIVARS IN DRYLAND FARMING - Karshiev Alisher Eshmamatovich; Jananov Berdinazar Khudaynazarovich (Web of Journals Publishing, 2024)
In this article, the effect of planting dates on productive stalks and productive stems of new durum wheat varieties currently being planted in dry areas of our republic is highlighted, and recommendations are given on planting dates of new durum wheat varieties.
Keywords: Durum wheat, planting time, Mingchinor, Langar, Yoqut-2014 and Jawahir varieties, productive bunching, productive stalks.